Randomised controlled trial of interferon alfa (lymphoblastoid interferon) in chronic non-A non-B hepatitis. Issue 6666 (14th January 1989) - Jacyna, M. R.; Brooks, M. G.; Loke, R. H.; Main, J.; Murray-Lyon, I. M.; Thomas, H. C.
Abstract : OBJECTIVE--To determine the effect of low dose interferon alfa (human lymphoblastoid interferon) on aminotransferase activities in chronic non-A non-B hepatitis. DESIGN--Prospective randomised controlled parallel group study of active treatment versus no treatment carried out over 16 weeks and preceded by baseline measurements at weeks 8 and 4 and time zero. SETTING--HEPATOLOGY outpatient clinics in secondary referral centres. PATIENTS--Fourteen adults with histologically proved chronic hepatitis and persistently raised aminotransferase activities for six months or more. INTERVENTIONS--Seven patients randomised to receive interferon alfa 5 megaunits (MU) daily for one week, reducing to 5 MU thrice weekly for seven weeks, then 3 MU thrice weekly for eight weeks. Controls not treated. END POINT--Control of hepatic enzyme activity in chronic non-A non-B hepatitis. MEASUREMENTS AND MAIN RESULTS--Serum aspartate aminotransferase activity remained raised in controls (mean increase in study period 23.4 U/l) but fell rapidly to normal in the treated group (mean decrease 106.4 U/l). In four cases values were normal by eight weeks and in five cases by 16 weeks. Only minor side effects were recorded (fever, myalgia), which became less common as treatment progressed. CONCLUSIONS--Continuous low dose interferon alfa reduces aspartate aminotransferase activity to normal in most patients with chronic non-A non-B hepatitis and may prevent progression to cirrhosis.